Emergency and its understanding in biology - Bremer, Józef (Studia Ecologiae et Bioethicae, 2019)
After a review of the reductionist theories and the emergency theory, I will present Piotr Lenartowicz SJ’s understanding of the emergence observed in living organisms and his reference to the Aristotelian-Thomistic concept of the ‘soul’ (‘substantial form’). Next, I will compare this understanding to contemporary, philosophical–biological emergency theories that refer to the role of biological limitations in maintaining life and in the functioning of the organism. In conclusion, I will point out the fundamental differences in the understanding of emergency according to Lenartowicz and the authors of the aforementioned theories.